Wind turbine noise: development of an airfoil turbulent inflow noise prediction method based on Amiets theory. - Faria, Alexandre Martuscelli (2021)
The scientific community efforts in the field of renewable energy have been focused on avoiding an increase of the average global temperature that surpasses the 1.5C mark. In that scenario, wind energy had experienced a rapid and continuous growth in its installed capacity worldwide along the past two decades. This expansion however is bounded synchronously by multiple factors, such as land availability and impacts on the environment, fauna and people, once wind farms are being pushed more and more to the vicinity of inhabited areas. One of the major concerns regarding newer technologies of horizontal axis wind turbines is maintaining the noise level in line with each local noise control regulations. As noise level is direct proportional to the wind turbine rotor diameter, and newer blades are becoming larger and larger because of the simultaneous increase on power output, it is mandatory to adopt the noise emission as a wind turbine blade design constraint and look after new blade geometries that combine both aerodynamic and aeroacoustic efficiency. PNoise is an airfoil and wind turbine noise prediction module developed at Poli-USP by Poli-Wind group in collaboration with TU-Berlin QBlade wind turbine blade design software. PNoise, through a 2D mathematical modeling, takes into account the sources of airfoil noise combined in order to have an accurate spectrum prediction and contribute to the design of quieter blades without lowering the power output. Airfoil noise consists of a synchronized effect of multiple sources, being the main sources the airfoil self-noise and the turbulent inflow noise. The mathematical modeling and integration of the latter within QBlade code is the main objective of this study. The turbulent inflow noise is caused by the interaction between turbulent scales and the airfoil surface. It tends to be dominant over airfoil self-noise in the low to mid frequency range (up to 2000 Hz) and is very sensitive to the pair turbulence integral length scale and intensity. Central to this study are the application of Amiet theory and its extensions, and also the discussion regarding turbulence spectrum modeling considering the usual von K´arm´an homogeneous and isotropic turbulence assumption and Batchelor rapid distortion theory (RDT) that adds anisotropy effects on noise. As it is known, atmospheric turbulence conditions are hardly obtained in a aeroacoustic tunnel setup, and so a distinct turbulence spectrum may be observed in each case. Therefore, both may be covered by PNoise novel turbulent inflow noise prediction method.